GIS Based Area Appropriateness Modeling for Rural Development: A Study of Paktika Province, Afghanistan - Hazrat Mohammad Wahdaty; Hameedullah Mohammadi (Randwick International of Social Science Journal, 2022)
In order to clearly determine the viability of rural development in Afghanistan's Paktika province, the information on land use planning that the locals may provide is collected. Spatial planning is crucial for the province of Paktika's rural development. Effective spatial planning enables entities including national and state governments, business developers, communities, and people avoid duplication of effort. The structural and basic improvements of their planning systems have made spatial planning possible.This study uses an integrated GIS-AHP model to identify the province of Paktika's best rural growth locations. The outcome demonstrates that the GIS-AHP model is a useful tool for rural planning and location selection. To determine the best location for rural development, seven factors were taken into consideration: slope, road, land use, river, water areas, cultivated areas, and soil. Final results indicate that 13535.3 sq. km was extremely suitable, 4563.2 sq. km was moderately acceptable, 889.5 sq. km was marginally suitable, and 348 sq. km was not suitable for the rural development of Paktika province.